ERROR IN FIGURES OF PHYSICS TEXTBOOKS FOR 10TH GRADE IN HIGH SCHOOL - KARTIKA SARI, WIDYA; , DWIKORANTO (Inovasi Pendidikan Fisika, 2019)
This research aims to show the error in figures of physics textbooks for 10th-grade high school Physics textbooks on Newtons Law topic. Data collecting technique is a literature review and Physicists interview. Concepts in textbooks are compared to concepts in Physics University textbooks and clarified with the experts. Collecting data, reducing data, presenting data, concluding and verifying data are used as data analysis techniques. Based on the analysis result, error found in the figure of force diagram in three conditions of the object and in the figure of force diagram in the elevator in Pujianto, Risdiyani Chasanah, and Supardianingsih textbook, entitled Buku Siswa Fisika SMA/MA Kelas X published by Intan Pariwara on 2016. In Marthen Kanginans textbook entitled FISIKA Untuk SMA/MA Kelas X published by Erlangga on 2016, error found in the figure of action-reaction force direction in the runner. In Ketut Kamajaya & Wawan/Purnamas textbook entitled Buku Siswa Aktif dan Kreatif Belajar Fisika Untuk SMA/MA Kelas X which is published..by Grafindo Media Pratama on 2016, error found in the figure of force diagram in the inclined surface.Keywords: error, figures, textbook, Newton?s Law.